(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
The rapid integration of digital learning tools has significantly transformed teaching and learning processes in higher education institutions worldwide. Technologies such as learning management systems, virtual classrooms, educational applications, and multimedia resources have reshaped instructional delivery and student engagement. This study examines the impact of digital learning tools on students’ academic performance in higher education. Using a quantitative research design, data were collected from undergraduate and postgraduate students across multiple disciplines. Statistical analysis reveals a positive relationship between the use of digital learning tools and academic performance, particularly in terms of conceptual understanding, learning motivation, and assessment outcomes. The findings suggest that strategic adoption of digital technologies can enhance educational effectiveness, though challenges related to accessibility, digital literacy, and overdependence remain. The study contributes to the growing body of multidisciplinary research on educational technology and provides insights for educators and policymakers.